Sexual dimorphism in the relationship between Forkhead-Box P2 and BMI with cognitive deficits in schizophrenia - Yang, Mi; Cui, Ying; Xue, Mei; Forster, Mattew T.; Lang, Xiaoe; Xiu, Meihong; Li, Zezhi; Zhang, Xiangyang (Frontiers in Aging Neuroscience, 2022)
FOXP2, cognitive deficits and schizophrenia are associated with neurodegenerative pathophyisiology. Mounting evidence suggests that body mass index (BMI) and FOXP2 may contribute to cognitive deficits in schizophrenia. However, the sex difference in the contribution of FOXP2 and BMI, as well as their potential interaction with cognitive deficits in schizophrenia, has not been investigated. A total of 867 schizophrenia patients and 402 controls were recruited. Cognitive function was assessed using the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). The polymorphism rs10447760 of the FOXP2 gene was genotyped. Male schizophrenia patients had superior language performance compared to female patients (F= 17.83; pBonferroni < 0.0001). BMI was positively associated with language scores in male patients with schizophrenia (ß=0.60, t=3.30, p=0.001), as well as in patients with schizophrenia who carried the FOXP2 rs10447760 CC genotype (ß=0.53, t=3.16, p=0.002). Interestingly, this association was only found in male patients with schizophrenia who also carried the FOXP2 rs10447760 CC genotype (ß=0.63, t=3.44, p=0.001). Our study reveals a sex difference in the language deficits of schizophrenia patients, and shows sexual dimorphism in the contribution of FOXP2, BMI and their interaction to cognitive deficits in patients with schizophrenia.